1996
DOI: 10.1143/jjap.35.l359
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Concentration in the Top Silicon Layer of Silicon-on-Insulator Materials Formed by Low-Dose Implantation of Oxygen

Abstract: Oxygen concentration in the top silicon layer of silicon-on-insulator materials formed by low-dose implantation of oxygen has been measured by means of secondary ion mass spectroscopy. A value of less than 1×1017 atoms/cm3 has been obtained. We propose that the oxygen concentration in the top silicon layer is controlled by oxygen out-diffusion during the wafer cooling process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…But in our low-dose SIMOX, it has been confirmed that oxide precipitates hardly exist in the top Si layer. 23 The latter signal may be "new donors" formed at higher temperatures (650-750°C) than thermal donors.2425 When the magnetic field was parallel to the .100> direction, the spectrum of the implanted sample showed two peaks at p = 2.0055 and 2.0036. Overlap of these peaks shields the dependence of their p values on the rotation angle of the magnetic field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But in our low-dose SIMOX, it has been confirmed that oxide precipitates hardly exist in the top Si layer. 23 The latter signal may be "new donors" formed at higher temperatures (650-750°C) than thermal donors.2425 When the magnetic field was parallel to the .100> direction, the spectrum of the implanted sample showed two peaks at p = 2.0055 and 2.0036. Overlap of these peaks shields the dependence of their p values on the rotation angle of the magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…'6 In n-metaloxide-semiconductor field effect transistors (n-MOSFET5), however, parasitic bipolar effects degrade their performance; for example, abnormal lowering of threshold voltage and drain-to-source breakdown voltage. To overcome this problem, methods such as using a lightly doped source,' a SiGe narrow-bandgap source, 23 and without an Ar dose of 2 X iO' cm2 are shown in Fig. i.…”
Section: Introductionmentioning
confidence: 99%
“…Gosele et al2': the BOX growth by ITOX requires an oxygen concentration in the top Si layer above the equilibrium solubility limit. The latter was recently confirmed by calculations of the oxygen concentration in the top Si layer during TTOX 22. Oxygen oversaturation of the silicon should prevent the solubility driven oxygen depletion of the BOX.…”
mentioning
confidence: 62%